Phosphodiesterase inhibitors in the treatment of sepsis and septic shock (Research, Society and Development, 2021)
Sepsis is a prevalent syndrome defined as a life-threatening organ dysfunction caused by a host's unregulated response to an infection, which can manifest itself in several ways. The pathophysiology of the syndrome involves the inflammatory and immunological pathways, and the response of the circulatory system plays a fundamental role in ischemia and organic injury. Phosphodiesterase inhibitors (iPDE) act by increasing the levels of cyclic nucleotides (cAMP and / or cGMP). These agents promote several effects according to their selectivity, among them: vasodilation, increased cardiac output, decreased endothelial permeability, inhibition of pro-inflammatory cytokines, and inhibition of coagulation. In view of this, the hypothesis was raised that iPDE could be beneficial in the treatment of sepsis. Clinical studies that used iPDE agents to treat sepsis show promising results. Animal models have been used to investigate the mechanisms involved in the pathology of sepsis, as well as new therapeutic options. The phosphodiesterase enzyme is classified in 11 families, and the research is focused on non-selective PDE inhibitor drugs, iPDE-3, iPDE-4 and iPDE-5. Two main septic models are used: application of Escherichia coli lipopolysaccharide and ligation and cecal puncture surgery. The drugs are administered intraperitoneally or intravenously before sepsis induction, in different doses. Despite the large number of positive results, the differences found between the septic models show the need for standardization of methods to obtain reliable data that can be used in clinical research.